Trauma and its representations : the social life of mimesis in post-revolutionary France - Jenson, Deborah (Johns Hopkins University Press, 2001)
The author argues that mimesis not only denotes the representation of reality, but is also a crucial concept for understanding the production of social meaning within specific historical concepts.